STUDY OF THE PROCESSES OF WASTEWATER TREATMENT FOR REUSE IN THE PULP AND PAPER INDUSTRY - HALYSH, Vita; RADOVENCHYK, Iaroslav; GOMELYA, Mykola; RADOVENCHYK, Vyacheslav (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Nowadays, more than 80% of cardboard and paper products of Ukrainian mills are made from waste paper - secondary fibers that differ in their chemical and physical properties from primary cellulosic fibers. Characteristic feature of secondary fibers is the presence of a large number of small fibers, which negatively affects the quality of finished products, mass retention on the grid during the formation of paper or cardboard, which leads to pollution of wastewaters. Despite its environmental friendliness and economy, waste paper is also characterized by the presence of various pollutants, the formation of which is associated with the process of paper formation, storage of finished products, and their use. As a result of the preparation of the mass from secondary fibers, there is a transition of pollutants from the waste paper to the wastewater in the form of colloidally dispersed and soluble substances, which lead to the pollution of circulating water. Purification of water and its reuse in technological processes is an important task of paper industry mills. The results show that more than 90% of the secondary fibers have a length that does not exceed 1 mm, while in the primary cellulose fiber from coniferous wood about 53% of the fibers have a length of more than 1 mm. The high content of short fibers in the paper mass affects the processes of paper formation, worsening them, and a decrease in the retention of the fiber on the grid of the paper or cardboard machine is observed, causing the pollution of wastewater. The results of the study of coagulation of industrial wastewater with the content of suspended solids 1520 and 3200 mg/dm3 from the production of cardboard from recycling paper show that the best coagulants are A1(OH)C12 and A12(OH)5C1. The maximum efficiency of water purification of only 92.5% was achieved at the suspended solids content of 1520 mg/dm3, while for wastewater with a suspended solids concentration of 3200 mg/dm3 98.0% was obtained. To develop a scheme for deep purification of wastewaters, it is important to understand which components are removed from water more easily and which are more difficult during coagulation. For this purpose, studies on coagulation of model suspensions of starches, bentonite and kaolin using inorganic coagulants were conducted. It was established that coagulation of native corn starch suspension with inorganic coagulants is effective. However, in the case of using modified starches, the removal of cationic starches is reduced. The efficiency of water purification in the removal of bentonite by sedimentation-filtration with the use of coagulants is quite high. The degree of purification reaches 80.8-98.1%. The filtering stage allows the degree of purification to be further increased. Research on the processes of purification of model kaolin suspensions shows that mechanical and physico-chemical methods are ineffective in removing this mineral filler.
Keywords: primary fiber; secondary fiber; cardboard; strength indicators; wastewater; coagulants